Legislative Dynamics of Religious Courts and Compilation of Islamic Law in Indonesia Analysis of Busthanul Arifin's Thoughts - Is, Muhammad Fadhlan; Ediz, M.Hidayat; Sarianto, Debi (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
The Religious Courts Law and the Compilation of Islamic Law serve as guidelines for resolving cases in the Religious Courts. The drafting of religious justice laws and the drafting of Islamic law in Indonesia involved several important stages and key figures. One of the important figures in the preparation and formulation of laws regarding religious justice and the preparation of Islamic law is Busthanul Arifin. This research aims to explain Bustanul Arifin's ideas and thoughts which color the formulation of religious laws and the preparation of Islamic law in Indonesia. This research uses a qualitative method with a content analysis approach. The research findings explain that Busthanul Arifin's thoughts greatly influenced the formation of religious justice laws and the drafting of Islamic law. There are three important thoughts of Busthanul Arifin, namely first; institutionalization of Islamic law can avoid differences in the application of Islamic law. Second, the institutionalization of Islamic law can be carried out by increasing the authority and function of religious courts. Third, the institutionalization of Islamic law is to uphold justice and strengthen the Indonesian state based on Pancasila, not to create an Islamic state. Knowing and understanding Busthanul Arifin's thoughts on Islamic law legislation in Indonesia through the judiciary will provide an understanding that unity in the application of Islamic law is a solution to avoid legal dualism and strengthen the upholding of justice and is by Pancasila.